Potential impacts of climate change on the environmental services of humid tropical alpine regions - Buytaert, Wouter; Cuesta Camacho, F.; Tobón, Conrado (Wiley, 2011)
Humid tropical alpine environments are crucial ecosystems that sustain biodiversity, biological processes, carbon storage and surface water provision. They are identified as one of the terrestrial ecosystems most vulnerable to global environmental change. Despite their vulnerability, and the importance for regional biodiversity conservation and socio-economic development, they are among the least studied and described ecosystems in the world. This paper reviews the state of knowledge about tropical alpine environments, and provides an integrated assessment of the potential threats of global climate change on the major ecosystem processes.